Mutagenicity Study of Pandanus Conoideus Oil - Maeda, Takanori; Miyakita, Haruka; Goto, Manami; Ito, Akemi; Wijaya, Hendra; S. Surono, Inggrid; Nishigaki, Toshiaki (Warta Industri Hasil Pertanian, 2013)
Pandanus conoideus (buah merah or tawi) is exclusively grown in Papua island and its neighbor areas, and indigenous people have been consuming it as functional food for thousand years. We have reported safety and anti-tumor effects of Buah Merah extract oil (S.B.M) in experimental animals. However, mutagenicity or genotoxicity of S.B.M has not been evaluated. We carried out mutagenetic evaluation of S.B.M by in vitro Ames test using salmonella typhimuriumÂ  TA98, TA100, TA1535 and TA1537 and escherichia coli WR2uvrA with or withou the activation of S9 mixture. Concentrations used for this test were 313-500ug/plate. The results show that there is no increase in revertant colonies, suggesting that S.B.M has no mutagenic activities under the conditions of this study.